21 century learning skills revisited - a conceptual paper on leaving 'gaps' and going deep - Kjærgaard, Thomas; Dau, Susanne (Proceedings of the International Conference on Networked Learning, 2018)
This paper revisits the 21st-century learning skills (21CLS) and discusses the need to leave 'gaps' in the curriculum while pursuing chosen topics more in-depth. The paper suggests ways to choose both 'gaps' and in-depth topics; furthermore, the paper investigates relevant technologies for bridging the gaps and for going deep. The paper discusses the connection between 'Das Exemplarische Prinzip' (exemplary teaching) and what may be interpreted to be the initial thoughts behind the formulation of the 21CLS presented in the document 'A Nation at Risk'. The two concepts are separated by three decades (1951 'Tübinger resolution -1981 'A Nation at Risk'). However, they share the same conviction that not every bit of knowledge available can be taught/learned and, furthermore, that some knowledge is more important than other. We wish to revisit this notion because we believe that the advances in Artificial Intelligence (AI) and the automation of increasingly complex processes in our everyday lives will influence education. This indicates that we may need to adjust the topic- and activity-selection principles that teachers and curriculum developers deploy to select what to teach and what to outsource to networked learning and digital learning materials. The discourse of the 21CLS seems to have materialised into a specific practice in Denmark, a practice that embraces programming exercises (Dot/Dash, LEGO Mindstorms, Scratch, Python etc.), tinkering with electronics, playing computer games, 3D printing and Laser cutting in workshops called 'Maker spaces'. The 21CLS, in a Danish context, are distilled into; Collaboration, Critical Thinking, Creativity, Communication (the 4Cs). In our research and in the development projects in schools we have taken part in, we have the positive experience that the way the 21CLS are practiced in a Danish context gave some pupils a sense of pride in their products and that some pupils acted more as designers of solutions for real problems than as pupils doing school work. On a more negative note, the 21CLS activities may come across as isolated events with little connection to curriculum or exams. Finally, we raise the discussion of how Teacher Education can develop a practice that incorporates the convictions of the 21CLS in other ways. We suggest a focus on technology that supports dialogue and reflection and bridges both knowledge 'gaps' and time and space 'gaps'. Furthermore, we suggest learning designs that revisit 21CLS as a framework for learning to learn.